Recommendations for Dose Selection for Adolescent Patients in Relevant Adult Oncology Clinical Trials. Issue 4 (21st November 2021) - Leong, Ruby; Liu, Qi; Li, Lingjue; Liu, Jiang; Ren, Yunzhao R.; Lee, Peter; Chuk, Meredith; Reaman, Gregory; Wang, Yaning
Abstract : Our research supported the dose selection recommendations for adolescents in the US Food and Drug Administration (FDA) Guidance on Inclusion of Adolescent Patients in Adult Oncology Clinical Trials. The FDA Guidance states that for drugs administered as a flat dose in adults and data showing no clinically meaningful effect of body size on drug exposure and toxicity in adults, a minimum body weight threshold may need to be defined to prevent adolescents who have a lower body weight from exceeding adult exposures. Our review of adult population pharmacokinetic analyses of new molecular entities approved for oncology between January 2015 and March 2021 suggested that 40 kg (the approximate median body weight of a 12‐year‐old) is generally the lower end of the body weight range that has no clinically relevant effect on drug pharmacokinetics or safety. The minimum body weight threshold and selection of an appropriate dose for adolescents in relevant adult oncology clinical trials should ultimately be determined based on available data on pharmacokinetics or pharmacodynamics of the investigational drug with consideration of body size effect on drug exposure, toxicity, and efficacy data (if available), the therapeutic index of the drug, and dose‐ and exposure‐response relationships in adults.